ANTIMALARIAL COMPOUNDS FROM ENDOPHYTIC FUNGI OF BROTOWALI (Tinaspora crispa L) - Elfita Elfita; Muharni Muharni; Munawar Munawar; Leni Legasari; Darwati Darwati (Indonesian Journal of Chemistry, 2011)
The term endophytic refers to a bacteria or a fungi microorganism that colonizes interior organs of plants, but does not have pathogenic effects on its host. In their symbiotic association, the host plant protects and feeds the endophytic, which ";in return"; produces bioactive metabolites to enhance the growth and compotitiveness of the host and to protect it from herbivores and plant pathogens. Plants with ethnobotanical history, for example brotowali (Tinaspora crispa L), are likely candidates to find bioactive compounds. Two alkaloids have been isolated from endophytic fungi of brotowali. The molecular structures of the isolated compounds were determined based on spectroscopic data, including UV, IR, NMR 1D and 2D spectrum. The compounds were determined as: 7- hydroxy-3,4,5-trimethyl-6-on-2,3,4,6-tetrahydroisoquinoline-8-carboxylic acid (1) and 2,5-dihydroxy-1-(hydroxymethyl)pyridin-4-on (2). The compound has antimalarial activity against Plasmodium falciparum 3D7, with IC50 values 0,129 µM and 0,127 µM.